PAKAIAN SEBAGAI PELINDUNG SURYA - SHW, Tantari (Fakultas Kedokteran Universitas Brawijaya, 2003)
ABSTRACT Although sunlight is of much benefit for live, it has an adverse effects on human skin. The effects of sunlight can be controlled by using protective cream or reducing the exposure to sunlight. Appropiate design clothes and correct protective factorsare part of efforts can prevent all spectrum of UV rays. The clothes’s protective nature depend on it’s fibre’s struvture, colour, waterproof properties, as well as it’s refine processes. Personal protection towards Ultraviolet radiation can be further supported by wearing a big cap, using an umbrella, being under a shade, using appropriate protective clothes and avoiding the sunlight between 10.00 am until 04.00 pm. The above steps should be initiated at an children. In every country including Indonesia, there should be standarritation and regulation concering protective steps towards sunlight.